Institutionalising Human Governance Determinant: Steering Organizations towards Sustainability - Hanapiyah Z.M.; Daud S.; Wan Abdullah W.M.T. (Institute of Physics Publishing, 2023)
Empirical studies; Internal controls; empirical analysis; governance approach; institutional framework; leadership; organizational framework; research work; sustainability